A Descriptive Study on the Role of Sponsorships in Events in Building the Image of a Brand: The Impact of Sponsorships on Brand Image in Events (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Events have been around us forever. The word ‘event’ has come from the Latin word ‘eventus’ which means ‘outcome, result, success.’ Events include a large variety of social gatherings, meetings, sports, shows and performances and play an important role in our society. Any happening or an activity can be referred to as an Event and acts as a good platform to showcase or promote new or existing productsservices. For instance, celebration of religious or cultural festivals like Ganeshotsav, Durga Puja, Dussehra, Kumbh Mela, Rann Utsav etc. are all events. A wedding ceremony, T20 World Cup, launch of a new product by an organization or a Farewell party organized by junior students in a college or school are all different types of events. The research paper revolves around how sponsoring the right kind of events could help and benefit the brands build their image and attract more serious audience with quantifiable results.